The usefulness of transrectal endosonography in differentiating an anal abscess from a rectal carcinoma - Kolodziejczak, Malgorzata (Radiology and oncology (Ljubljana), 2005)
Background. The high anal abscess might have not a typical, chronic clinical course, and its diagnosis may be difficult. Case report. The authors describe a case of a patient with the initial diagnosis of rectal cancer. Because of non-specific clinical symptoms suggesting a high anal abscess with atypical , chronic course of the disease, additional investigations were suggested. The final diagnosis was high, submucous-intersphincetric abscess. Conclusions. In the described case the most important ones turned out to be an exact finger per rectum examination, clinical proctologic assessment, and the transrectal ultrasound.
Keywords: Absces; Abscess; Diagnosis, Differential; diagnostika; Diagnostika diferencialna; Endosonografija; Endosonography; karcinom; Middle Age; Proctitis; Proktitis; Rectal Neoplasms; rektalne bolezni; Rektalne novotvorbe; rektum; Srednja leta; ultrazvočna diagnostika